STUDY ON USAGE OF FABRIC REMNANTS ON YEMENI’S FASHION FOR WOMEN - Budoor Mohammed Thabit; Hanisa Hassan (INTERNATIONAL JOURNAL OF HERITAGE, ART AND MULTIMEDIA (IJHAM), 2024)
The big quantity of fabric remnants was thrown away in Yemen due to a lack of knowledge and competency in reusing the remnants as material for making clothes. It has become a burden to the consumers and also bad for the environment. Therefore, this research aims to understand why the seamstress in Yemen wasted a lot of remnants and the possibility of using the remnants in making innovative designs on Yemenis traditional clothing such as Abaya and Galabiah. In order to answer the objectives, the researcher applies the qualitative approach in order to describe and understand the problems stated for this study by made several interviews with Yemeni’s respondent who used to be a seamstress in Yemen, besides her personal experience when working in the workshop in Yemen. The prior objective is to recognise what was done to remnants in sewing workshops. Secondly, the researcher will be producing a design line using remnants with various techniques of embellishment to create new designs for Yemen’s traditional costume of Abaya and Galabiah. The researcher hopes that through her innovation can inspire other designers or seamstress to use remnants as a source of material in making clothes. At the end of this study, the researcher found out that her Yemeni’s respondents threw away remnants because they do not have the knowledge and skill to turn remnants into fashion. Plus, they are also lazy to think of recycling remnants since they had lots of orders from clients. In the end, the researcher made a questionnaire about the final designs and they did agree that remnants can be used to make beautiful traditional Yemeni’s dress. Since remnants came from different sources, the design made is unique and one-off, which is the preference for most Yemenis. The researcher also proved that innovative and creative thinking are vital in creating designs, and hopefully it can change the perspective of Yemeni women towards the usage of remnants in fashion.